English around the World, Number 7 - English-Speaking Union of the U. S., New York, NY.; McCulloch, John J. B.; English-Speaking Union of the U. S., New York, NY. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1972)
This newsletter continues to report on the use and instruction of English throughout the world. Articles here concern the status and role of English in Zaire, Portugal, Taiwan, Israel, Tanzania, and Burundi. One report discusses the work and scope of the Center for English Language Research and Teaching in Beirut; another article reports on several projects in Australia dealing with teaching English to migrants. (VM)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: English (Second Language); Language Acquisition; Language Instruction; Language Role; Newsletters; Second Language Learning; Status